Crisis familiar y Bienestar Psicológico en jóvenes de 18 a 25 años de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Manzano Moyano, Santiago Gerardo (2021)
The current research project aimed to analyze the family crisis and its relationship with the psychological well-being of young people between the ages of 18 and 25 in the first and seventh semesters of the career of psycho-pedagogy. Understanding that the family crisis is characterized by the family dissolution, where the old models and capacities are not adequate for a long time and a change is required, while psychological well-being is associated with positive effects, such as happiness, that is, being good with oneself, be aligned with the motivations and objectives that structure their lifestyle. Methodologically, the research was conducted with a quantitative approach, which used a non-experimental design, descriptive, correlational, basic and field type. The sample consisted of students from 18 to 25 of the psych pedagogy career of the “Universidad Nacional de Chimborazo.” The methods used were psychometric tests and the scales of social climate in the Family (FES) and psychological well-being (EBP). Through which it was possible to obtain the data that allowed to generate the analysis of the results. Through the SPSS, a Pearson correlation of 0.304 was established, which suggests that students with a medium level of concern for the family crisis have a tough time developing their psychological well-being. Therefore, conflicts and problems that may arise in the family environment directly affect the self-concept and the empathy generating in people difficulties to adapt appropriately to various environments.